Association between COVID‐19 and telomere length: A bidirectional Mendelian randomization study. Issue 11 (29th July 2022) - Huang, Danqi; Lin, Siqi; He, Junting; Wang, Qi; Zhan, Yiqiang
Abstract: Several traditional observational studies suggested an association between COVID‐19 and leukocyte telomere length (LTL), a biomarker for biological age. However, whether there was a causal association between them remained unclear. We aimed to investigate whether genetically predicted COVID‐19 is related to the risk of LTL, and vice versa. We performed bidirectional Mendelian randomization (MR) study using summary statistics from the genome‐wide association studies of critically ill COVID‐19 ( n  = 1 388 342) and LTL ( n  = 472 174) of European ancestry. The random‐effects inverse‐variance weighted estimation method was applied as the primary method with several other estimators as complementary methods. Using six single‐nucleotide polymorphisms (SNPs) of genome‐wide significance as instrumental variables for critically ill COVID‐19, we did not find a significant association of COVID‐19 on LTL ( β  = 0.0075, 95% confidence interval [CI]: −0.018 to 0.021, p  = 0.733). Likewise, using 97 SNPs of genome‐wide significance as instrumental variables for LTL, we did not find a significant association of LTL on COVID‐19 (odds ratio = 1.00, 95% CI: 0.79–1.28, p  = 0.973). Comparable results were obtained using MR‐Egger regression, weighted median, and weighted mode approaches. We did not find evidence to support a causal association between COVID‐19 and LTL in either direction.